Effect of Project-Based Learning (PjBL) on Students’ Creative Thinking in IPAS Education - Nurlinda Safitri; Patmawati Patmawati; Nurul Fatmanisa; Anita Julia Asri (MASI Mandiri Edukasi, 2025)
Students’ creative thinking is essential for 21st-century education, particularly in science (IPAS). This research seeks to ascertain how implementing the PjBL (project-based learning) approach improves pupils' creative thinking in science learning. This study is a quasi-experimental study with a quantitative approach. A quasi-experimental pretest-posttest control group design with 44 fourth-grade students was used. The sample consists of fourth-grade students at SDN Gunung Gede Elementary School in Bogor City, specifically Class IV B and Class IV C, with 44 students, using non-probability sampling (saturation sampling). Data collection in this research employs tests, observations, and documentation. Data analysis utilizes the Independent Sample t-test. The study results indicate that the Project-Based Learning (PjBL) model significantly affects students' creative thinking skills. The experimental class using PjBL significantly outperformed the control group (p = 0.001). It can be concluded that PjBL improves students’ creative thinking in IPAS learning.